From Fragment Hit to Clinical Candidate: Discovery of Dual H1R/H4R Ligands with Superior Efficacy in Allergic Conjunctivitis - Peter Weber; Rogier Smits; Herman D. Lim; Mounir Andaloussi; Jac Wijkmans; Bas de Boer; Thuy Duong Tran; Barbara Zarzycka; Mabel E. Dekker; Tiffany van der Meer; Rick Riemens; Niels Hauwert; et al. (Journal of Medicinal Chemistry, 2026)
Abstract Dual inhibition of the histamine H1 and H4 receptors (H1R and H4R) has been shown to provide superior anti-inflammatory efficacy in preclinical models of allergic disease compared to selective inhibition of either receptor alone. Building on this concept, we initiated a fragment-based discovery program and previously identified a quinazoline-containing fragment hit. Here, we describe the lead optimization toward compounds with unique dual H1R/H4R activity. Structure–activity relationship studies yielded potent and balanced ligands with nanomolar affinities for both receptors, as well as pharmacokinetic properties suitable for ocular administration. Among these, quinazoline 35.HCl (GD136) and tetrahydroquinazoline 72.HCl (GD134) demonstrate robust in vivo efficacy in a ragweed-induced mouse model of allergic conjunctivitis, significantly reducing hyperemia and outperforming selective H1R or H4R antagonists. Based on its pharmacological profile, ADME properties, ease of formulation, and in vivo efficacy, GD134 was selected as the clinical development candidate for a first-in-class dual-targeted therapy of allergic conjunctivitis.